The Influence of Leadership and Organizational Culture on Employee Performance Mediated by Interpersonal Communication - Sugiyanto, Eko; Ekowati, Sri; Finthariasari, Meilaty; Harini, Ririn; Yuniarti, Rina; Pitra, Ahmad (Journal of Social Work and Science Education, 2024)
The purpose of this research is to answer and solve the research problems outlined above, including the following: to analyze the influence of leadership, organizational culture, and interpersonal communication on employee performance; the impact of leadership on employee performance; the effect of organizational culture on employee performance; and the role of interpersonal communication in mediating the relationship between leadership and organizational culture on employee performance. In this research, the method used is quantitative. The population used in this study consisted of all Civil Servants in South Bengkulu Regency, totaling 5,617 individuals. Based on the results of the sample calculation, the minimum sample size to be used in this study is 365 samples. The research concludes that leadership has a positive effect on interpersonal communication, organizational culture positively affects interpersonal communication and interpersonal communication influences employee performance. Additionally, leadership and organizational culture also have a positive impact on employee performance, and interpersonal communication can mediate this relationship.